ASSESSMENT OF THE EFFICACY OF NEUROPROTECTICVE THERAPY FOR NEWBORNS WHO SURVIVED ASPHYXIA - Pokhylko, V.I.; Kovaliova, Ye.M.; Kaliuzhko, Ye.A.; Korobka О.V.; Chernyavskaya, Yu.V. (World of Medicine and Biology, 2012)
The paper presents results of a randomized study of clinical efficacy of a therapy complex with additional administration of сerakson as compared to standard therapy for newborns after asphyxia. The research indicates that the inclusion of сerakson in standard therapy for newborns with hypoxic-ischemic affliction of the CNS after perinatal asphyxia enhances adaptive and compensatory reactions of participants under the influence of stress factors and facilitates a speedier restoration of their active and passive tonus.